2018
DOI: 10.1002/cbdv.201700459
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biorelevant Media Components on Dissolution Behaviour of 1,2,4‐Thiadiazole Derivative Designed for Alzheimerʼs Disease Prevention

Abstract: In this study, dissolution behaviour of 1,2,4-thiadiazole derivative (1-[5-(3-chloro-phenylamino)-1,2,4-thiadiazol-3-yl]-propan-2-ol) displaying an anti-Alzheimer activity was examined in biorelevant media such as Simulated Gastric Fluid (SGF, pH 1.2), Fasted State Simulated Gastric Fluid (FaSSGF, pH 1.6) and Fasted State Simulated Intestinal Fluid (FaSSIF, pH 6.5). It was found that solubility and dissolution rate of 1,2,4-thiadiazole derivative under consideration are not strongly dependent on pH, whereas th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…The presence of inert formulation excipients can sometimes have an effect on the solubility of certain compounds. In addition, it has been shown that certain components of simulated biorelevant media may form micelles which may enhance solubilization of a drug molecule (36).…”
Section: In-vivo Dissolution and Absorption Mechanistic Model Predictionmentioning
confidence: 99%
“…The presence of inert formulation excipients can sometimes have an effect on the solubility of certain compounds. In addition, it has been shown that certain components of simulated biorelevant media may form micelles which may enhance solubilization of a drug molecule (36).…”
Section: In-vivo Dissolution and Absorption Mechanistic Model Predictionmentioning
confidence: 99%